Role of early serum beta human chorionic gonadotropin measurement in predicting multiple pregnancy and pregnancy wastage in an in vitro ET fertilization cycle - Neeta Singh; Anjuman Ara Begum; Neena Malhotra; Anupama Bahadur; P Vanamail (Wolters Kluwer Medknow Publications, 2013)
Objective: This study was performed to assess the prognostic value of serum beta human chorionic gonadotropin (βhCG), measured on day 14 post embryo transfer (ET) for predicting multiple gestation and pregnancy wastage in women undergoing in vitro fertilization ET (IVF-ET). Materials and Methods: This retrospective study was performed between May 2009 and November 2012. Out of the 181 women who conceived, 168 were included and the remaining 13 were excluded as their pregnancy was biochemical. Serum βhCG was measured using a chemiluminescent enzyme immunometric assay. The predictive values of serum βhCG for establishing multiple pregnancy and pregnancy wastages were calculated by receiver operating characteristic (ROC) curve analysis. Median values of serum βhCG and outcome of all pregnancies were compared. Results: Out of the 168 patients who conceived after IVF treatment, 114 (68%) were viable pregnancies (delivered/ongoing). Among the viable pregnancies, 97 (85%) had a successful pregnancy outcome and the remaining 17 patients are ongoing pregnancies. Median values of βhCG (625 IU/L) among viable pregnancies was significantly (P < 0.05) higher than that of nonviable pregnancies (174 IU/L). The median values of βhCG for singleton (502 IU/L), twins (1093 IU/L), and triplets (2160 IU/L) was statistically significant (P < 0.05). Using ROC curve it was predicted that for a value of βhCG at 375 IU/L, the sensitivity of viable pregnancy was 65% and specificity of viable pregnancy was also 65%, with positive and negative predictive values of 65 and 68%, respectively. Similarly for multiple pregnancy and pregnancy wastage the predictive values of βhCG were 808 and 375 IU/L, respectively; while the sensitivity and specificity is more than 65% each. Conclusion: βhCG cutoff values determined on day 14 post ET by ROC curve analysis are useful in discriminating between multiple pregnancy and pregnancy losses. The cutoff value might aid in the prognosis, clinical management, and counseling of the IVF patients.